The effects of cattle manure and NPK fertilizers on soil physical properties and growth performance of zea mays cv. Thai supersweet / Norhayati Marzuki - Marzuki, Norhayati (Faculty of Plantation and Agrotechnology, 2014)
A field experiment was conducted at Sharefarm of UiTM Arau Perlis on January 2014, to compare the effects of NPK fertilizer, cattle manure, and NPK fertilizer + cattle manure mixture on the physical properties and growth performance of Zea mays cv. Thai Supersweet. Five (5) treatments applied to the soil were (T0) no fertilizer application and act as a control, (T1) 200 kg/ha of NPK fertilizer, (T2) 15 t/ha of cattle manure, (T3) 15 t/ha of cattle manure + 200 kg/ha of NPK fertilizer, (T4) 22.5 t/ha of cattle manure + 200 kg/ha of NPK fertilizer. There were laid out in a Randomized Completely Block Design (RCBD). The plot size was 3 m x 1.3 m with 1.5 m as the distance between the plots. The growth parameters recorded were plant height, stem girth, number of leaves and leaf area. Data were collected from the 2nd to the 8th week after planting (WAP). Soil analysis carried out was more focus on the soil physical properties such as soil moisture, soil bulk density, soil particle density, soil color, soil porosity, and soil texture were conducted. A corn performance of plant height, plant girth and number of leaves were higher at (T3) 15 t/ha of cattle manure + 200 kg/ha of NPK fertilizer with 164.19 cm, 25.91 mm and 14 numbers of leaves per plant respectively. The leaf area was examined higher at (T4) 22.5 t/ha of cattle manure + 200 kg/ha of NPK fertilizer with 376.26 cm2. This study recommended using 15 t/ha of cattle manure + 200 kg/ha of NPK fertilizer to get a better performance of corn growth. The combination moderate of organic fertilizer and NPK fertilizer appeared to be the most beneficial application compared with the other treatments.